1991
DOI: 10.1128/jb.173.20.6626-6631.1991
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella aerogenes catabolite gene activator protein and the gene encoding it (crp)

Abstract: The catabolite gene activator protein from Klebsiella aerogenes (CAPK) and the corresponding protein from Escherichia coli (CAPE) were shown to be nearly identical. Both CAPK and CAPE activated transcription from the CAP-dependent promoters derived from E. coli and K. aerogenes. The crp gene from K. aerogenes (encoding CAP) is tightly linked to rpsL. The nucleotide sequence of crp predicts an amino acid sequence for CAPK that differs in only one position from that of CAPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…This 972 nucleotide open reading frame has coding sequence for a protein of 324 residues which differs from the S. typhimurium and E. coli CysB proteins in only 15 and 21 positions respectively; most of the amino acid replacements are conservative. This degree of sequence identity among homologous proteins from the three species is lower than that observed for the catabolite activator protein (Osuna and Bender, 1991), but significantly higher than that observed between the 8-galactosidase genes of K. aerogenes and E. coli (Buvinger and Riley, 1985).…”
Section: Resultscontrasting
confidence: 55%
“…This 972 nucleotide open reading frame has coding sequence for a protein of 324 residues which differs from the S. typhimurium and E. coli CysB proteins in only 15 and 21 positions respectively; most of the amino acid replacements are conservative. This degree of sequence identity among homologous proteins from the three species is lower than that observed for the catabolite activator protein (Osuna and Bender, 1991), but significantly higher than that observed between the 8-galactosidase genes of K. aerogenes and E. coli (Buvinger and Riley, 1985).…”
Section: Resultscontrasting
confidence: 55%
“…Addition of cAMP to the growth medium overcomes glucose-mediated catabolite repression of histidase formation in K. pneumoniae (124). Mutants defective in the genes for adenylate cyclase (cya) or CRP (crp) cannot activate hut expression in response to carbon limitation (115,124). In vitro transcription with purified components showed that both CRP and cAMP were necessary (and sufficient) to activate transcription from hutUp, the hutU promoter (115,116).…”
Section: Enteric Bacteriamentioning
confidence: 99%
“…Mutants defective in the genes for adenylate cyclase (cya) or CRP (crp) cannot activate hut expression in response to carbon limitation (115,124). In vitro transcription with purified components showed that both CRP and cAMP were necessary (and sufficient) to activate transcription from hutUp, the hutU promoter (115,116). The hutUp region contains two CRP-cAMP-binding sites: a stronger site centered at position Ϫ82.5 (relative to the start of transcription) and a weaker site centered at position Ϫ42.5 (116,117).…”
Section: Enteric Bacteriamentioning
confidence: 99%
“…The resulting 655-bp product was cloned into the expression vector pET24b with the restriction sites that had been introduced with the primers. Sequence analysis of two of the resulting pET-CRP plasmids revealed two positions that differed from the published sequence of K. aerogenes crp (29). These differences did not cause a change at the protein level, however.…”
Section: Vol 183 2001 Catabolite Repression Of Citrate Fermentationmentioning
confidence: 84%
“…6). It should be mentioned that a very small proportion of the purified protein was probably E. coli CRP, which differs, however, from K. pneumoniae CRP in only one position (29). The corresponding proteins were shown to be completely interchangeable with respect to activation of the E. coli lacZ and the K. pneumoniae hutU promoters (30).…”
Section: Vol 183 2001 Catabolite Repression Of Citrate Fermentationmentioning
confidence: 97%